Kriminalisasi dalam Ruang Siber: Antara Perlindungan Negara dan Ancaman terhadap Kebebasan Sipil - Saparudin Saparudin (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2026)
The criminalization policy in cyberspace in Indonesia faces a fundamental dilemma between the state's need to protect its citizens from digital crimes and the threat to civil liberties and human rights. This research critically examines four dimensions of cyber criminalization: its concept and development in criminal law, the urgency of state protection, implications for civil liberties, and the reconstruction of fair policies by considering Constitutional Court Decisions Number 105/PUU-XXII/2024 and 115/PUU-XXII/2024. Using normative legal methods with a juridical-normative approach through library research, this study analyzes primary, secondary, and tertiary legal materials descriptively-analytically. The findings reveal that structural imbalances in cyber criminalization policies stem from the dominance of security approaches that neglect procedural justice principles and participatory oversight mechanisms, exacerbated by gaps in law enforcement officers' understanding at the implementation level. The progressive Constitutional Court decisions provide positive signals for protecting civil liberties, yet their impact on law enforcement practices still requires strict supervision. This research concludes that balancing state security and civil liberties can only be achieved through three main pillars: independent judicial oversight, substantive public participation, and effective remedy mechanisms for aggrieved citizens.